Differences of the effect of thermal treatment in an oxygen-containing gas medium on properties of the surface layer Ti, Zr, Hf - Trush Vasyl; Fedirko Viktor; Luk’yanenko Aleksander; Stoev Petro; Tikhonovsky Mykhail; Kovtun Kostiantyn (Lviv Politechnic Publishing House, 2019)
The paper presents the characteristics of the surface layer of d-elements of the IV group (titanium, zirconium and hafnium) after thermal diffusion saturation from a controlled oxygen-containing gas medium. Saturation was carried out at T = 750 °C for t = 5 hours at different pressures (P = 1.33∙10–1 Pa, P = 1.33∙10–2 Pa, P = 1.33∙10–3 Pa). Experimentally revealed differences in the characteristics of the surface layer of titanium, zirconium and hafnium. It was shown that a hardened diffuse layer is formed with a higher hardness relative to the metal core in the reverse order of their affinity for oxygen. On titanium, zirconium and hafnium, only a diffuse layer is formed without a phase film. The appearance of the surface of the samples before and after processing is given. According to the results of the study, chemical-thermal treatment in an oxygen-containing gas medium leads to changes in the surface layer of sheet material from titanium, zirconium and hafnium. The state of the surface layers directly affects the characteristics of finished products, in particular, fatigue life. Therefore, this treatment is a good tool for controlling the state of the surface layers of the aforementioned metals, and then their properties.
Keywords: titanium, zirconium hafnium, oxygen medium, surface layer, microhardness